The Simpsons : Second Season Disc 4 - Matt, Groening; Azaria, Hank.; Harry ShearervMarcia Wallace; Julie Kavner; Nancy Cartwright; Yeardley Smith; Dan Castellaneta (USA 20th Century Fox Television, 1989)
The Simpsons are very politically incorrect family. Homer works with pride in a nuclear power plant run with more regard for profit that safety. His wife is Marge, a kind of supermom. They have three kids: Bart, an underachiever (""and proud of it""), Lisa (who is as serious and responsible as Bart isn't), and Maggie.
The satiric adventures of a working class family in the misfit city of Springfield.
Language: English
Subtitles: English, Norwegian, Swedish
Keywords: Comedy -- Tv Series; Animation